An Evaluation of an Emotion Regulation Programme for People with an Intellectual Disability. Issue 3 (19th August 2014) - McWilliams, Jenna Louise; de Terte, Ian; Leathem, Janet
Abstract : Purpose: The aim of the study was to examine the effectiveness of the Transformers programme on individual's use of appropriate emotion regulation strategies. Design/methodology/approach: Five people with an intellectual disability participated in the Transformers programme and took part in the current study. The intervention was evaluated using the Profile of Anger Coping Skills and incident reports. The Profile of Anger Coping Skills was completed by participants and their caregivers. Findings: The majority of participants demonstrated increases in self- and caregiver-reported use of appropriate emotion regulation strategies following their involvement in the Transformers programme. However, treatment gains were not always maintained at follow-up. Three of the participants also exhibited fewer incidents of challenging behaviour after taking part in the programme. Originality/value: Overall, the results provide preliminary support for the continued use of the Transformers programme with people with an intellectual disability who have emotion regulation difficulties. It is recommended that further research be carried out with a larger sample size, a control group, and longer follow-up period.